Self-compassion to decrease performance anxiety in climbers: A randomized control trial - Philipp Röthlin; Romaine Leiggener (Bern Open Publishing, 2021)
In climbing, anxiety may impair performance. Using an evolutionary approach, we hypothesized that athletes who treat themselves with self-compassion activate their contentment and soothing system and thus reduce their performance anxiety. A two-week randomized control trial was used to investigate the effect of self-compassion on somatic and cognitive anxiety. We compared two groups (intervention and waiting list) on two dates. Sixty climbers (Mage = 27.95, SDage = 8.57) completed the pre- and post-assessment. The intervention consisted of a psychoeducational leaflet and five self-compassionate writing tasks. In the posttest, the self-compassion intervention group showed increased self-compassion (F = 4.33, p = .04, ηp2 = 0.07) and decreased somatic performance anxiety (F = 6.24, p = .02, ηp2 = 0.10) compared to the waiting list control group. We found no changes in cognitive performance anxiety. The results suggest that self-compassion could be considered as a possible intervention to reduce physical symptoms of performance anxiety.